Application of Microbial Geochemical Exploration Technology in Identifying Hydrocarbon Potential of Stratigraphic Traps in Junggar Basin, China - Li Ding; Yubing Wu; Xuechao Liu; Fenfen Liu; Harry Mei (AIMS Geosciences, 2017)
Even though three-dimension seismic has been widely applied in the eastern slope of Fukang sag with several fluvial channel sand bodies identified as in Jurassic Toutunhe group, the hydrocarbon charge of these stratigraphic traps is hard to predict and still of great uncertainty. Microbial geochemical exploration technology (MGCE), which detects the microbial and geochemical anomalies in surface soil, was applied to delineate three hydrocarbon play fairways, identify six favorable prospects and to predict the geochemical properties of the reservoirs at depth. The results of MGCE survey agreed well with the drilling results of 10 wells and demonstrated the applicability and effectiveness of MGCE in the exploration of stratigraphic traps in this area. Furthermore, the integration of geology, geophysics, geochemistry and geo-microbiology, so-called 4G exploration, led to the discovery of the Qigu group as a new hydrocarbon-bearing play in late Jurassic formation in this area. MGCE technology and 4G integrated exploration has not only made the breakthrough of Qigu discovery, but also opened a new model for stratigraphic reservoir exploration in the area.